Refining Interview Protocols for Online Interviews on the Employment of Persons with Down Syndrome : Insights from a Pilot Test. - Md Mizanur, Rahman; Abg, Safuan; Sharifa Ezat, Wan Puteh; Razitasham, Safii; Chen, Yoke Yong; Rosalia, Saimon; Ting, Chuong Hock (Cambridge University Press, 2024)
This chapter explores and provides guidance on the e-Delphi method, and challenges in ethical recruitment, data management, and security.